MARKET COMMUNICATION: Speech Styles and Language Use in the South Tangerang Traditional Market - Yasmiandi, Fauzan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The use of language in everyday life has many forms and styles, depending heavily on demographics, people's habits, and conditions. So you can often find a variety of language styles and ways of pronouncing them, because actually there is an emotional message to be conveyed, so that the meaning can be understood. One example of where the use of various languages ​​is often found is the market. The market is a place for interaction between traders and sellers, so in the context of selling their products, traders in interacting with prospective buyers instinctively carry out various developments in the use of words and language styles, in order to attract the attention of prospective buyers. This study aims to describe the model of communication between sellers and buyers in traditional markets. To answer these objectives, a qualitative approach is used with descriptive methods. The object of research is the Ciputat traditional market, South Tangerang. In the process of collecting data, observation techniques were used, namely seeing, recording, listening, and interacting with traders and buyers at the Ciputat market. The results of the study show that there is a tendency to use certain languages ​​and speech styles, according to their respective regions of origin. This is done as a form of natural adaptation with the aim that there is an emotional bond, resulting in buying and selling transactions.